2021
DOI: 10.1556/1326.2020.00789
|View full text |Cite
|
Sign up to set email alerts
|

Extraction process and method validation for bioactive compounds from Citrus reticulata cv. Chachiensis: Application of response surface methodology and HPLC–DAD

Abstract: Citrus reticulata cv. Chachiensis, a traditional Chinese herb, has extensive medicinal and edible effects. 3′,4′,5,6,7,8-Hexamethoxyflavone (HM) and 5,6,7,8,4′-pentamethoxyflavone (PM) are main bioactive compounds in Chachiensis, which have been reported to possess various biological properties. In this study, supercritical CO2 extraction (SCE) and high-speed countercurrent chromatography (HSCCC) were utilized to prepare HM and PM from Chachiensis. The contents of target compounds were determined by a high-per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Conclusively, the TMCA extraction efficiency was greatly affected by sonication time and methanol-to-material ratio. Furthermore, a lack-of-fit p -value of 0.1297 indicated that the lack-of-fit was not significantly related to pure error [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Conclusively, the TMCA extraction efficiency was greatly affected by sonication time and methanol-to-material ratio. Furthermore, a lack-of-fit p -value of 0.1297 indicated that the lack-of-fit was not significantly related to pure error [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…At present, the process conditions used in the production are as follows: the reaction temperature is 45 • C, reaction time is 10 min, and the ratio of the zinc powder dosage to Cd content is 3:1. In order to further analyze the influence rules of the above three main influencing factors and their interaction on the Cd removal rate, find the optimal process parameters and provide scientific guidance for production, this paper uses Design-Expert software to design a total of 17 experimental sites with three factors and three levels [8][9][10][11][12][13]. The factors and levels in the scheme are shown in Table 1 below.…”
Section: Experimental Designmentioning
confidence: 99%
“…However, the results of the study showed that the typical compounds in each type of mandarin orange could be different even though they came from the same species (Wang et al 2021). In addition, most of the reported data regarding the compounds present in the RGL citrus species are the result of HPLC, so it has not been possible to analyze large amounts of bioactive compounds simultaneously (Abeysinghe et al 2007;Mei et al 2021).…”
Section: Introductionmentioning
confidence: 99%